Implikasi Metode Mentoring Halaqah dalam Pembentukan Akhlak Siswa Madrasah - Siregar, Zulfikar Ali Buto (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
Research to explore the implications of the ḥalaqah mentoring method in Islamic Religious Education, particularly in shaping the character of Madrasah students. Ḥalaqah is considered a holistic approach, encompassing spiritual and emotional intelligence aspects, to strengthen faith foundations and shape Islamic character. This qualitative research focuses on descriptive qualitative research aimed at describing phenomena or events naturally occurring in the research location, specifically at Madrasah Aliyah in the Aceh region. Data were collected through participatory observation, in-depth interviews with ḥalaqah mentors and students, as well as the analysis of documents related to ḥalaqah activities and student achievements. Data processing is carried out using analytical techniques that include data reduction, data presentation, and conclusions. The research findings indicate that ḥalaqah, as an effective mentoring method, shapes the character of Madrasah students. Diverse ḥalaqah materials involving spiritual and emotional intelligence aspects have a significant positive impact. The role of ḥalaqah mentors and the empowerment of ROHIS as co-mentors are key to success in creating a supportive learning environment. Based on the research findings, strengthening the ḥalaqah program with an emphasis on emotional intelligence integration can be an effective step in reinforcing character formation. Furthermore, it is recommended to involve more stakeholders, including parents and madrasah committees, to support the comprehensive implementation of ḥalaqah.